Pengembangan Sistem Informasi Administrasi Kependudukan Desa Gumelem Wetan Berbasis Website - Ghufron Zaida Muflih; Rifki Ardiansah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Gumelem Wetan Village is a village in Susukan District, Banjarnegara Regency which is located ± 36 Km from the city center. In the implementation of population administration in Gumelem Wetan Village for population data processing from recording, making certificates to reporting population data, births, deaths, and moves is still manual bookkeeping. This of course reduces the effectiveness and efficiency of population data management. Technology, information and communication have developed very rapidly, this must be used to facilitate the management of population data in Gumelem Wetan Village because technology can provide convenience for humans in various aspects of life. In Indonesia, almost all companies and institutions, both government and private, have sophisticated data processing technology, so the presence of information technology is very necessary. Unlike the data processing in Gumelem Wetan Village which is still bookkeeping, a website-based population administration information system is needed for Gumelem Wetan Village that is able to manage population data effectively and efficiently. So that it can facilitate the performance of the Gumelem Wetan Village Government apparatus. In addition, it can also improve public services, especially administrative services for the people of Gumelem Wetan Village. This study used interviews, literature review, and observation as data collection methods. While the system development method uses the waterfall method using the PHP (Hypertext Preprocessor) programming language. The output of this research is a website-based population administration information system in Gumelem Wetan Village. Keywords: Population Administration Information System, Gumelem Wetan, Data Processing, PHP, Waterfall Method